Persistent T cell unresponsiveness associated with chronic visceral leishmaniasis in HIV-coinfected patients - Vrij, Nicky de; Pollmann, Julia; Rezende, Antonio M.; Ibarra-Meneses, Ana V.; Pham, Thao-Thy; Hailemichael, Wasihun; Kassa, Mekibib; Bogale, Tadfe; Melkamu, Roma; Yeshanew, Arega; Mohammed, Rezika; Diro, Ermias; et al. (Communications biology, 2024)
A large proportion of HIV-coinfected visceral leishmaniasis (VL-HIV) patients exhibit chronic disease with frequent VL recurrence. However, knowledge on immunological determinants underlying the disease course is scarce. We longitudinally profiled the circulatory cellular immunity of an Ethiopian HIV cohort that included VL developers. We show that chronic VL-HIV patients exhibit high and persistent levels of TIGIT and PD-1 on CD8+/CD8- T cells, in addition to a lower frequency of IFN-γ+ TIGIT- CD8+/CD8- T cells, suggestive of impaired T cell functionality. At single T cell transcriptome and clonal resolution, the patients show CD4+ T cell anergy, characterised by a lack of T cell activation and lymphoproliferative response. These findings suggest that PD-1 and TIGIT play a pivotal role in VL-HIV chronicity, and may be further explored for patient risk stratification. Our findings provide a strong rationale for adjunctive immunotherapy for the treatment of chronic VL-HIV patients to break the recurrent disease cycle.
Gesehen am 28.03.2025